Food waste management practices in hospital foodservices and their associated greenhouse gas emissions: potential for increased environmental sustainability - Yip, Yee Man Janis; Cook, Nathan; Collins, Jorja (Frontiers in Nutrition, 2025)
IntroductionHospitals produce and waste large amounts of food. When disposed in landfill it creates greenhouse gases (GHGs) from the decomposition process. While various food waste management strategies exist that divert hospital food waste to an alternative end of life pathway to landfill, it is not clear which can decrease GHG emissions the most. This study aimed to (a) compare the differences in GHG emissions associated with hospital foodservice food waste before and after adopting a food waste management strategy, and (b) identify which waste management strategy can prevent the most GHGs in 1 year.Materials and methodsA secondary analysis of data from a systematic review reporting on food and food-related waste diversion strategies in hospital foodservice was conducted. The online “ReFED Impact Calculator” was used to calculate GHG emissions from food waste in the original scenario (e.g., landfill), and the alternative scenario after a food waste management strategy that reused, recycled or recovered resources was implemented. The net change of GHGs was calculated, and the GHGs emissions avoided in paired samples and between food waste management scenarios was analyzed statistically.ResultsFifty-five food waste management strategies (surplus food donation, feeding animals, anaerobic digestion or industrial uses, and composting) were eligible for analysis and were grouped into eight scenarios. The median GHGs generated decreased after adopting the alternative strategy in all scenarios. There was a statistically significant median reduction in GHGs when changing from landfill to donations (−11.54, p < 0.001), landfill to industrial uses (−25.92, p < 0.001), and landfill to composting (−15.24, p < 0.001). Percentage change in GHGs generated in these 3 scenarios demonstrated a significant difference (p < 0.001), with landfill to donations displaying the greatest reduction in GHGs (−92.02%), followed by composting (−8.69%) and industrial uses (−7.75%).ConclusionVarious food waste diversion strategies can handle types and volumes of hospital food waste, yet each strategy displays a reduction in GHG emissions compared to a lower prioritized strategy. Donating waste shows the greatest reduction in GHG emissions and if food waste cannot be avoided, it may be the preferred end of life pathway for food waste.